A decision support system for supplier selection for Indian textile industry using analytic hierarchy process based on fuzzy simulation. (1st January 2011) - Kumar, Darshan; Singh, Jagdev; Singh, Om Pal
Supplier selection is arguably one of the most critical functions for the success of an organisation in today's competitive scenario. Both qualitative and quantitative factors are considered and a trade off is made between tangible and intangible factors while selecting a supplier. This selection is one of the decisions which determine the long-term viability of the organisation. Literature reveals that many methods have been used to objectively evaluate suppliers including analytic hierarchy process (AHP). Considering drawback of AHP that it handles crisp values only, use of AHP based on fuzzy simulation (FSAHP) has been proposed in this paper. The weights of criteria and sub-criteria of alternatives have been represented by fuzzy linguistic variables and fuzzy simulation has been used to estimate the expected value of fuzzy weights of different alternatives for the decision analysis of three suppliers for a textile-based industry.